Evaluation of Olfactory Fossa Depth Using Computed Tomography in A Tertiary Center: A Retrospective Study - Shrestha, Robinson; Gautam, Mahesh; Shrestha, Nischal (Nepalese Journal of Radiology, 2023)
Introduction:Endoscopic sinus surgery is a widely utilized surgical method for addressing chronic sinonasal diseases. To prevent major postoperative problems, an anatomical understanding of its variants is necessary. Our study aims to determine the occurrence and classification of different Keros types by analyzing paranasal sinus CT scans and retrospectively evaluating the depth of the olfactory fossa in our population.Methods:This is a retrospective single-centre analytical study on 254 patients who had undergone a non-enhanced paranasal sinus CT scan for 1 year after ethical approval from the Institutional Review Committee of Nobel Medical College Teaching Hospital. The statistical program SPSS version 25 was used to conduct the statistical analysis.Results:The average depth of the right olfactory fossa (OF) was 4.4±1.44 mm on the right side and 4.5±1.5 mm on the left side. According to the Keros classification, out of a total of 254 patients, 38 patients (15%) were classified as Keros I, 193 patients (76%) as Keros II, and 23 patients (9%) as Keros III for the right lateral lamella. 44 (17.3%), 180 (70.9%), and 30 (11.8%) patients were classified as Keros I, II, and III respectively, for the left lateral lamella..Conclusions:A preoperative CT scan of the paranasal sinus is useful in assessing the architecture of the anterior skull base and making sure the surgical approach is properly planned.